A new species of Neottia (Orchidaceae, Epidendroideae) from alpine border region between China and Myanmar - Jin, Xiao-Hua; Pang, Hong-Bo (Phytotaxa, 2016)
Neottia nujiangensis, a new species from alpine border region between China and Myanmar, is described and illustrated. Neottia nujiangensis is sympatric and similar to Neottia fugongensis, but differs from it by having flowers densely along the rachis, pedicel and ovary about 5 mm long, lateral sepals ovate, petals elliptic, lip 4 mm long and not ciliate, lobelets widest at base, auricle dentate.